Covering Race and Religion: The Moorthy and Nyonya Tahir Cases in Four Malaysian Newspaper - Halimahton Shaari; Ngu Teck Hua; V. Raman (Kajian Malaysia, 2006)
Reporting on issues like race and religion in a multi-racial and multireligious society is not an easy media responsibility. In a country like Malaysia where racial and religious sensitivities abound, the media have to constantly tread on precarious ground, balancing between what to write and how to write it. Much of the concern over the reporting of sensitive issues stems from the belief that a wrong move may have dire consequences, as seen in the recent controversy and furore over the Prophet Muhammad caricature published in the Danish newspaper, Jyllands-Posten. This study analyses two recent racial/religious issues – M. Moorthy and Nyonya Tahir cases – as reported in the New Straits Times (NST), Utusan Malaysia (UM), Malaysia Nanban (MN) and Sin Chew Daily (SCD). The former case caused a stir when there was a tussle between Moorthy’s Indian/Hindu family and the Federal Territory Islamic Affairs Council which argued that Moorthy had converted to Islam when he was alive without the family’s knowledge. The latter was a case of a Malay/Muslim woman who, while alive, had denounced Islam and lived as a Chinese practising Buddhism. This study analyses how the two race and religion-related controversial issues were treated in the various language newspapers in Malaysia. A preliminary finding showed that, true to the communal nature of the Malaysian press, there was an apparent slant in how the ethnic press covered these two issues. For instance, in terms of prominence given to the stories, SCD, while downplaying the Moorthy story, dedicated more space to the Nyonya Tahir case. Similarly, MN highlighted the Moorthy story and downplayed the Nyonya Tahir case. The different newspapers were also seen to ''favour'' the subject they covered according to the ethnicity.